ANALISA FAKTOR YANG BERHUBUNGAN DENGAN PRAKTEK PENATALAKSANAAN IBU DI RUMAH PADA BALITA DIARE DI WILAYAH UPT PUSKESMAS MANDING KABUPATEN SUMENEP - Zakiyah Yasin (Wiraraja Medika : Jurnal Kesehatan, 2014)
Diarrhea is watery defecate  with frequent more than usually (more than there times/day). Much factors had related with diarrhea of childreen cases in Manding of primary health center, sumenep district.This study using cross sectional study design with 60 sampel result simple random sampling in manding of primary health center area. Analysis using sperman correlation and chi square . varable study are age of mother, education level of working of mother, knowledge of mother.It was revealed that correlation betwee education level of mother with treatment in home by mother (p=0,000), had correlated between knowledge of mother with treatment in home by mother (p=0,002), had correlated betwee working of mother (p=0,003)Is was concluded this study that faktor had related with diarrhea of childreen diarrhea is eduation level, knowledge, working from mother’s childreen. Good knowledge will help on diarrhea, so health officer increase to assessment about diarrhea treatment to increasing as knowledge of mother. Keywords: diarrhea, childreen